2020
DOI: 10.3390/toxins12090556
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing Reveals Virulence Potentials of Helicobacter pylori Strain KE21 Isolated from a Kenyan Patient with Gastric Signet Ring Cell Carcinoma

Abstract: Helicobacter pylori (H.pylori) infection is etiologically associated with severe diseases including gastric cancer; but its pathogenicity is deeply shaped by the exceptional genomic diversification and geographic variation of the species. The clinical relevance of strains colonizing Africa is still debated. This study aimed to explore genomic features and virulence potentials of H. pylori KE21, a typical African strain isolated from a native Kenyan patient diagnosed with a gastric cancer. A high-quality circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 93 publications
1
14
1
Order By: Relevance
“…In the study Mwangi et al, conducted in 2020, they stated that the H. pylori strain they isolated from a patient in Kenya was similar to Asian stains. Although the main virulence factors they detected were found in other African strains, it was reported that this strain was not similar to other African strains in terms of phylogeny (26). In our study, we found that our results were similar in terms of virulence factors, ORF and phylogenies, but that African strains we studied generally differed from European and Asian strains in terms of both virulence gene prevalence and phylogeny.…”
Section: In Silico Analysis Of H Pylori From Different Continentscontrasting
confidence: 58%
“…In the study Mwangi et al, conducted in 2020, they stated that the H. pylori strain they isolated from a patient in Kenya was similar to Asian stains. Although the main virulence factors they detected were found in other African strains, it was reported that this strain was not similar to other African strains in terms of phylogeny (26). In our study, we found that our results were similar in terms of virulence factors, ORF and phylogenies, but that African strains we studied generally differed from European and Asian strains in terms of both virulence gene prevalence and phylogeny.…”
Section: In Silico Analysis Of H Pylori From Different Continentscontrasting
confidence: 58%
“…In Ethiopia, an East African country, reports on the diagnosis of HPI are largely based on serology and SAT [87,88,[107][108][109]. On the other hand, Kenya, a neighboring country, has reports on the use of SAT [89,90], endoscopy, RUT, histol-ogy, and culture [91,110]. Similarly, in Uganda, SAT [92], endoscopy, histology and RUT [93,94], serology and SAT [95] have been used in the diagnosis of HPI.…”
Section: Non-invasive Invasivementioning
confidence: 99%
“…The final detection was performed with POD/TMB substrate (Nacalai Tesque, Inc., Japan). This ELISA system was optimized and calibrated using the training set of blood samples from Congolese patients whose H. pylori status was already established using culture, histology or rapid urease test applied as previously described (S2 Table) [31,33,34]. Polyclonal rabbit anti-Helicobacter pylori IgG (Dako, Danmark) with detection by 1:80,000 peroxidase-conjugated secondary anti-rabbit IgG antibodies (Jackson Immuno Research Laboratories, Inc; USA) was used as an internal positive control while water, PBS and carbonate buffer were set as negative controls during all reactions.…”
Section: Development Of the Hpafr-elisa And Laboratory Testingmentioning
confidence: 99%